Nature-Inspired Synthesis of Yeast Capsule Replicas Encased with Silica-Vinyl Functionality: New Fluorescent Hollow Hybrid Microstructures - Beata Miksa; Katarzyna Trzeciak; Slawomir Kaźmierski; Artur Rozanski; Marek Potrzebowski; Krystyna Rozga-Wijas; Lukasz Sobotta; Magdalena Ziabka; Magdalena Płódowska; Karol Szary (Molecules)
Yeast capsules (YCs) produced from Saccharomyces cerevisiae with encapsulated fluorescent phenosafranin and azure dyes were used as catalytic template guides for developing hybrid functional organic/inorganic hollow microstructures with silica (SiO2) deposited on their surface generated in the imidazole-buffered system without the addition of any cationic surfactant. YCs-doped with SiO2 act as fluorescence emitters maintaining dye-loaded materials by sealing the microporous surface of YCs. We used vinyltrimethoxysilane as a precursor of SiO2 endowed with functional vinyl groups facilitating their further modification without disturbing the polysaccharide wall integrity. Consequently, the hybrid fluorescent polysaccharide/silica microcapsules (YC@dye@SiO2) are promising for wide-ranging optoelectronic applications in electrochromic and OLED devices with biocompatibility and biodegradability properties.